8 May 2020 - The race to develop a COVID-19 vaccine - Nene, Vishvanath M. (International Livestock Research Institute, 2020)
Vish Nene, co-leader of the Animal and Human Health Program at ILRI, gives an update on vaccines and treatment options under development for COVID-19. This film was recorded on 8 May 2020. Read more: https://www.ilri.org/news/good-and-no... Find ILRI expertise and resources on zoonoses: ilri.org/zoonoses